Analisis Sektor Ekonomi Unggulan dan Sektor Potensial Terhadap Pertumbuhan Ekonomi Kota Bengkulu Tahun 2016-2020 - Tika Oktariyani; Ellya Revolina; Teguh Dwi Arsyah (Universitas Batanghari, 2023)
GRDP growth plays a very important role in every economic sector that contributes to regional income and other economic factors. With the large contribution made by each sector to the GRDP of a region, it will be able to increase economic growth in a more advanced direction, increasing economic growth can improve welfare and meet the needs of the community. This study uses Location Qoutient (LQ) analysis to determine the base sector (leading), Klassen Typology to determine the potential sector, and Shift Share to determine the shift of leading sectors and potential sectors. The results of the Location Qountient analysis show that there are 11 leading sectors and 6 non leading sectors, the results of the Klassen typology analysis have 3 potential sectors that can still develop and the results of the shift share analysis show a shift and the city of Bengkulu has 4 sector classifications Bengkulu City has great potential in leading and potential sectors that can still be further developed to support regional economic growth. The local government of Bengkulu City should utilize and develop the leading sector and its leading sub-sectors so that they can provide more value for economic development and improve the welfare of the surrounding community.